A holistic framework to embed good company practice for customer retention. Issue 2 (13th March 2017) - McCrory, Barbara; Pilcher, Nick; McMillan, Janice
Abstract : Purpose: The purpose of this paper is to detail a holistic practice based guiding framework for improving customer retention, which helps companies instil a customer service culture through encouraging them to concentrate on the three key areas of culture, continuous improvement (CI) and customer service. Design/methodology/approach: The Delphi technique, using three rounds of hour long in-depth semi-structured interviews at director level across a range of industries. This was done with nine directors, totalling over 30 hours of data requiring in excess of 200 hours to transcribe. Findings: In order to achieve customer retention, a holistic company approach underpinned by senior management buy-in is critical, with open communication, employee empowerment, and employing "the right" personnel. The framework is viable with specific organisation input and supplementation with ongoing customer research. Research limitations/implications: The framework has only been tested with the companies in the study, and requires testing in practice. As such, it has not covered the ability of companies to change, but has simply developed a framework to assist in identifying the areas that need to be reviewed when considering changing to focus on the customer. Practical implications: To use this approach to customer retention requires companies to amalgamate culture, customer service and CI equally alongside customer focussed leadership, as an underpinning for the ethos of the business. Originality/value: The Delphi technique in an in-depth systemised approach with directors revealed unanticipated and significant insights regarding the benefits of amalgamating and devoting equal weight to the three areas of culture, customer service and CI to improve quality in all these areas